Reporting and methodological quality of systematic reviews underpinning clinical practice guidelines for low back pain: a meta-epidemiological study - Khan, Adam; Roberts, Will; Frank, Landon; Lillie, Anna; Torgerson, Trevor; Pierce, Aaron; Relic, Aaron; Khattab, Abdurrahman; Bright, Trevor; Hartwell, Micah; Vassar, Matt (Frontiers in Pain Research, 2025)
BackgroundLow back pain (LBP) is the leading musculoskeletal disorder worldwide and a major cause of disability, health care utilization, and economic burden. Clinical practice guidelines (CPGs) aim to optimize care but depend heavily on systematic reviews (SRs). The reporting and methodological quality of SRs underpinning LBP CPGs remain unclear.ObjectivesTo conduct a meta-epidemiological assessment of the reporting and methodological quality of SRs cited in LBP CPGs and compare Cochrane vs. non-Cochrane reviews.Methods and designCross-sectional meta-epidemiological study. We identified English-language LBP CPGs published between 2017 and 2021 and extracted SRs underpinning therapeutic recommendations. Reporting quality was assessed using PRISMA and methodological quality using AMSTAR-2. Two reviewers performed masked, duplicate extraction with consensus resolution. Between-group comparisons used Wilcoxon rank-sum tests; prespecified subgroup analyses (by intervention domain) and an exploratory multivariable linear regression examined factors associated with PRISMA scores.ResultsEight CPGs cited 90 unique SRs. Mean PRISMA adherence was 83% (SD: 12.2); 39% of SRs met ≥90% of items. Mean AMSTAR-2 adherence was 79.3% (SD: 14.4); 24% were rated overall “high,” while 14% were “low/critically low.” Common deficits included protocol registration, justification of excluded studies, and assessment of small study/publication bias. Cochrane SRs (n = 22) had higher PRISMA (91% vs. 81%) and AMSTAR-2 (88% vs. 76%) scores than non-Cochrane SRs (both p < 0.001). Interventional technique SRs tended to have slightly lower PRISMA scores than pharmacologic SRs after adjustment, whereas noninvasive non-pharmacologic SRs were similar. In exploratory regression, higher AMSTAR-2 ratings and predominance of randomized trials were associated with higher PRISMA scores.ConclusionsSRs informing LBP CPGs show variable reporting and methodological quality with consistent shortfalls in protocol registration, exclusion justifications, and publication-bias assessment. Cochrane SRs outperformed non-Cochrane SRs yet comprised only a minority of the evidence base. Facilitating uptake of protocol registration, complete PRISMA-aligned reporting, transparent exclusion lists, and routine small-study bias assessment, alongside greater use of methodologically stronger SRs, could strengthen the evidentiary foundation of LBP guidelines.